The boy in the striped pajamas : a fable - Boyne, John, 1971- (London : Vintage, 2006)
Bored and lonely after his family moves from Berlin to a place called "Out-With" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.
Reprint. Originally published: Great Britain : David Fickling Books, 2006.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Auschwitz (Concentration camp) -- Juvenile fiction; Auschwitz (Concentration camp) -- Fiction; Friendship -- Fiction; Nazis -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; World War, 1939-1945 -- Jews -- Fiction; Fiction